Multiple SH3 domain interactions regulate NADPH oxidase assembly in whole cells. - de Mendez, I (1996)
Src homology 3 (SH3) domains mediate specific protein-protein interactions crucial for signal transduction and protein subcellular localization. Upon phagocyte stimulation, two SH3 domain-containing cytosolic components of the NADPH oxidase, p47phox and p67phox, are recruited to the membrane where they interact with flavocytochrome b558 to form an activated microbicidal oxidase. Deletion analysis of p47phox and p67phox in transfected K562 cells demonstrated multiple SH3-mediated interactions between p47phox and the transmembrane flavocytochrome b558 and also between the cytosolic components themselves. The core region of p47phox (residues 151-284), spanning both SH3 domains, was required for flavocytochrome-dependent translocation and oxidase activity in whole cells. Furthermore, translocation of p67phox occurred through interactions of its N-terminal domain (residues 1-246) with p47phox SH3 domains. Both of these interactions were promoted by PMA activation of cells and were influenced by the presence of other domains in both cytosolic factors. Deletion analysis also revealed a third SH3 domain-mediated interaction involving the C-termini of both cytosolic factors, which also promoted p67phox membrane translocation. These data provide evidence for a central role for p47phox in regulation of oxidase assembly through several SH3 domain interactions.